2021
DOI: 10.3389/fmicb.2021.703933
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Surveillance and Phylodynamic Analyses Reveal the Emergence of Novel Mutations and Co-mutation Patterns Within SARS-CoV-2 Variants Prevalent in India

Abstract: Identification of the genomic diversity and the phylodynamic profiles of prevalent variants is critical to understand the evolution and spread of SARS-CoV-2 variants. We performed whole-genome sequencing of 54 SARS-CoV-2 variants collected from COVID-19 patients in Kolkata, West Bengal during August–October 2020. Phylogeographic and phylodynamic analyses were performed using these 54 and other sequences from India and abroad that are available in the GISAID database. We estimated the clade dynamics of the Indi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In an analysis of the original variant, this lineage revealed 23 substitutions, most of which are discrete mutations ( Silva et al., 2021 ; Korber et al., 2020 ). Lineage B.1.618 was discovered for the first time in October of 2020, this variant contained E484K mutation with many other variations and showed substantial development in West Bengal, India, in April 2021 ( Biswas et al., 2021 ). On 23 April 2021, The PANGOLIN analysis identified 135 sequences in India ( Singh et al., 2021 ).…”
Section: Sars-cov-2 Vaccine and Variantsmentioning
confidence: 99%
“…In an analysis of the original variant, this lineage revealed 23 substitutions, most of which are discrete mutations ( Silva et al., 2021 ; Korber et al., 2020 ). Lineage B.1.618 was discovered for the first time in October of 2020, this variant contained E484K mutation with many other variations and showed substantial development in West Bengal, India, in April 2021 ( Biswas et al., 2021 ). On 23 April 2021, The PANGOLIN analysis identified 135 sequences in India ( Singh et al., 2021 ).…”
Section: Sars-cov-2 Vaccine and Variantsmentioning
confidence: 99%
“…The region-specific co-mutations in the three countries with high vaccine coverage were linked steadily all through time, with the frequencies in Israel and the USA increasing over time. This phenomenon indicated that the mutation patterns may be associated with the genetic background of the populations, or may be correlated to some feature change of the virus, e.g., infectivity, transmissibility and disease severity, just as a previous study demonstrated the possible association of co-mutations with the infection outcomes manifested in Indian patients [ 36 ]. As none of the linked sites were in the RBD, or even in the S gene, it was speculated that they may not be related to immune evasion.…”
Section: Discussionmentioning
confidence: 89%
“… 7 In the second wave, several deaths in India occurred due to “cytokine storm” in adults, while many children contracted the disease with mild to severe symptoms. 8 , 9 , 10 Whether this differential clinical outcome was due to host specific immunity alone or also due to viral genomic mutations, remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Two possibilities behind these variable symptoms are the virus genotype and the unique host genetic make‐up orchestrating their immune responses 7 . In the second wave, several deaths in India occurred due to “cytokine storm” in adults, while many children contracted the disease with mild to severe symptoms 8–10 . Whether this differential clinical outcome was due to host specific immunity alone or also due to viral genomic mutations, remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%